Paleoflood reconstruction in the Gale crater of Mars. Issue 9 (November 2013) - Kereszturi, A.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract Analyzing a fluvial channel and related depositional fan at its termination in the Gale crater of Mars, the eroded and the deposited volume determined tobe close to each other around 0.47 and 0.32 km3 respectively. Using the Darcy‐Weisbach equation and a sediment transport capacity characteristic for high‐speed rivers, the duration to erode the channel and build up the sediment were found between 1.5 hours and 3.3 days. The short period might indicate that this ancient river was ephemeral and does not suggest a long duration of wetter and warmer climate, and also addresses a question regarding the general view of long‐period fluvial erosion on Mars. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)